The Influence of Family and Preschool Education on Children’s Initiative - Mahliyo, Ernazarova (Journal of Innovation in Education and Social Research, 2025)
This article analyzes the role of the family and preschool education as key factors in the formation of a child’s personality, with particular emphasis on their influence on the development of children’s initiative. Children’s initiative is understood as a set of qualities such as independent thinking, proposing new ideas, initiating and planning play or activities independently, and attempting to solve problems. The family and preschool educational institutions (kindergartens) are considered important factors in the development of this quality. The study highlights the essence of children’s initiative, the psychological and pedagogical factors influencing it, family upbringing styles, and the significance of the conditions created in preschool institutions. Practical recommendations are proposed to support approaches that foster initiative in children.